Clause-sensitivity of inflectional morphology in L2 english / Yuji Shuhama - Shuhama, Yuji (Universiti Teknologi MARA, 2021)
The Interface Hypothesis (Sorace, 2000) developed in line with the Minimalist theory of grammar (Chomsky, 1995 et seq.) supports the view of L2 acquisition that syntactic properties are acquired early while the acquisition of interface properties is delayed. One of the interface properties is inflectional morphology on English verbs, which involves subject-verb agreement at the syntax-morphology interface. Previous studies have revealed that for learners of L2 English, acquiring third person singular -s is harder than regular past -ed due to the absence of meaningless morphemes in L1. However, one question has been disregarded: Where in a clause are these morphemes inserted more successfully? Given that subordinate clauses are more complex than main clauses, this study examines the clause-sensitivity of L2 inflectional morphology. 44 Japanese university students learning English as L2 were asked to complete a grammatical judgment test and write an essay about a specified topic. The learners' inflection pattern was surveyed through the test scores and text analysis of the essays. Results show that -s tends to be omitted regardless of clause types, but -ed is omitted more frequently in complement clauses than main clauses. These are due to negative L1 transfer on L2 inflectional morphology and our findings imply the importance of clauses as meaningful units in L2 grammar instructions.